Experimental study on pressure drop and ice blockage characteristics of ice slurry flow in big-diameter pipes - Bo Yang; Daoke Tang; Weixing Yuan; Xiling Zhao; Lin Fu (International Journal of Refrigeration, 2025)

Removal of multiple pollutants in air pollution control devices of a coal-fired boiler installed with a flue gas condensation scrubber - Tailin Chen; Lejun Deng; Yuzhong Li; Jingwei Li; Xiling Zhao; Lin Fu (Journal of Cleaner Production, 2024)

SLIT3 knockdown inhibited TGF-β-induced hepatic stellate cells activation by down-regulating YAP signal - Xiling Fu; Jiabao Chang; Damin Jiao; Mengying Zhu; Yuqi Ma (Molecular & Cellular Toxicology, 2023)
Objective Liver fibrosis is a chronic liver disease caused by a variety of pathophysiological. However, there are no effective treatments to combat it. HSCs are a major source of fibrotic cells and exploring the mechanisms of HSC activation may provide new strategies for the treatment of liver fibrosis. Objectives To explore the role and underlying mechanism of SLIT3 in HSCs fibrosis. Results GSE163211 dataset analysis identified aberrant expression of SLIT3 in NASH F1-F4 tissues and SLIT3 expression level was positively correlated with fibrosis-related proteins. In vitro experiments showed that TGF-β induced upregulation of SLIT3 in LX-2 cells. Knockdown of SLIT3 significantly inhibited TGF-β-induced α-SMA, COL1A2, and COL1A1 expression, inhibited excessive cell proliferation and migration, and suppressed YAP activity. Conclusion Collectively, our findings suggest that SLIT3 deficiency alleviates TGF-β-induced HSCs activation by inhibiting YAP activity.

RNA-seq for comparative transcript profiling in leaves of strawberry seedlings under salinity stress - Rui Zhang; Qiuli Du; Wenzhe Zhao; Long Yang; Dongmei Li; Xiude Chen; Wei Xiao; Xiling Fu; Chao Yang; Ling Li (Plant Biotechnology Reports, 2023)

Exogenous melatonin alleviates damage from drought stress in Brassica napus L. (rapeseed) seedlings - Jingjing Li; Liu Zeng; Yong Cheng; Guangyuan Lu; Guiping Fu; Haiqing Ma; Qingyun Liu; Xuekun Zhang; Xiling Zou; Chunsheng Li (Acta Physiologiae Plantarum, 2018)

Genome-wide identification of WRKY family genes in peach and analysis of WRKY expression during bud dormancy - Min Chen; Qiuping Tan; Mingyue Sun; Dongmei Li; Xiling Fu; Xiude Chen; Wei Xiao; Ling Li; Dongsheng Gao (Molecular Genetics and Genomics, 2016)